Perbandingan Efektivitas Model STAD, TGT, DAN TTW Terhadap Hasil Belajar IPA Siswa - Zelhendri Zen; Reflianto Reflianto; Syamsuar Syamsuar; Farida Ariani (Pedagogi: Jurnal Ilmu Pendidikan, 2023)
In recent years, interest in exploring the effectiveness of different cooperative learning models in promoting science learning outcomes for high school students has been increasing. The three most studied models are STAD (Student Teams Achievement Divisions), TGT (Teams-Games-Tournaments), and TTW (Think-Talk-Write). The purpose of this study was to compare the effectiveness of the STAD, TGT, and TTW models on science learning outcomes of class VII students in junior high school. The research method was an experimental study with a comparative design. The results showed a significant difference in science learning outcomes among students taught using the three cooperative learning models. The TGT and TTW models did not show a significant difference in learning outcomes, although the TGT model showed better learning outcomes than the STAD and TTW models. This study also highlights the importance of considering specific learning objectives and student characteristics when selecting and adapting cooperative learning models. While the TTW and TGT models can be effective alternatives to the STAD model in improving science learning outcomes for junior high school students, further research is needed to explore the long-term effectiveness and generalizability of these models in different contexts